2017
DOI: 10.1515/aiht-2017-68-2957
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety culture shapes presenteeism and absenteeism: a cross-sectional study among Croatian healthcare workers

Abstract: Healthcare workers have high rates of injuries and illnesses at the workplace, and both their absence from work due to illness (absenteeism) or working ill (presenteeism) can compromise patient safety and the quality of health care delivered. Following this premise, we wanted to determine whether presenteeism and absenteeism were associated with patient safety culture (PSC) and in what way. Our sample consisted of 595 Croatian healthcare workers (150 physicians and 445 nurses) who answered the short-form WHO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 40 publications
1
23
0
1
Order By: Relevance
“…Insight was also provided by the study into the perceived legitimacy of different complaints as a reason for doctors to take sick leave. Findings showed that fatigue, even if extreme, would not be considered legitimate, although its potentially serious effects on job performance Croatia showing that staff in organisations with a stronger safety culture were more, rather than less, likely to work while sick 54 .These findings suggest that safety culture may over-ride the self-care of health professionals which will actually compromise rather than improve patient safety.…”
Section: Managing Presenteeismmentioning
confidence: 99%
See 1 more Smart Citation
“…Insight was also provided by the study into the perceived legitimacy of different complaints as a reason for doctors to take sick leave. Findings showed that fatigue, even if extreme, would not be considered legitimate, although its potentially serious effects on job performance Croatia showing that staff in organisations with a stronger safety culture were more, rather than less, likely to work while sick 54 .These findings suggest that safety culture may over-ride the self-care of health professionals which will actually compromise rather than improve patient safety.…”
Section: Managing Presenteeismmentioning
confidence: 99%
“…In such environments, it is particularly important to reframe taking F o r P e e r R e v i e w legitimate sick leave as responsible and healthy behaviour and presenteeism as a potential public health risk. Of some concern are the findings of aA recent study of healthcare workers in Croatia indicating that staff in organisations with a stronger safety culture were more, rather than less, likely to work while sick 54 .These findings indicate suggest that safety culture can over-ride the self-care of health professionals which will in fact compromise rather than improve patient safety.…”
Section: Managing Presenteeismmentioning
confidence: 99%
“…It is of particular concern in healthcare where there is a potentially serious public health impact due to the risk of cross-infection [3] to susceptible populations and excess morbidity and mortality [5,6]. Sickness presenteeism may compromise patient safety and the quality of healthcare delivered [7] and is associated with societal costs through productivity loss [8], impaired judgement [9] and an increased risk of medical errors [10]. An association between mental exhaustion and susceptibility to the common cold has also been reported [11].…”
Section: Introductionmentioning
confidence: 99%
“…Further research, which included doctors and nurses in two Croatian hospitals, found that nine PSC dimensions were graded strong, but it also found the dimensions Staffing and Nonpunitive Response to Error to be weak in both hospitals. The Hospital Management Support for Patient Safety dimension was found to be weak in one hospital [18].…”
Section: Introductionmentioning
confidence: 99%